Resposta :
Resposta:
Explicação passo a passo:
a)
x = 2 · (+7) + 5 · (-2)
x = 14 + (-10)
x = 14 - 10
x = 4
b)
x = 3 · (+8) - 7 · (-7)
x = 24 - (-49)
x = 24 + 49
x = 73
c)
x = 8 · (-5) - (-7) · (+2) - 3 - 4 · (-1) + 6
x = - 40 - (-14) - 3 - (-4) + 6
x = - 40 + 14 - 3 + 4 + 6
x = - 40 - 3 + 14 + 4 + 6
x = - 43 + 24
x = - 19
d)
x = 2 · (+10) + 5 · (-2) - 10
x = 20 + (-10) - 10
x = 20 - 10 - 10
x = 20 - 20
x = 0
e)
x = 3 · (-2) + 2 · (-7) + 13
x = - 6 + (-14) + 13
x = - 6 - 14 + 13 (sinais iguais, conserva o sinal e soma)
x = - 20 + 13 (sinais diferentes, mantem o sinal do maior e subtrai)
x = - 7